Pengaruh Pemasaran Digital Terhadap Peningkatan Penjualan dan Loyalitas Pelanggan (Studi Kasus dalam Brand Somethinc) - Carissa Maulidya Putri Hidayat; Delinda, Ribbi Aliya (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This study analyzes the impact of digital marketing on sales growth and customer loyalty in the Somethinc brand. Using a quantitative method with a sample of 103 respondents, the study found that digital marketing significantly contributed 50.8% to increased sales and customer loyalty. Marketing strategies such as social media, SEO, PPC, and content personalization play a crucial role in fostering closer interactions with customers. The analysis shows that digital marketing facilitates purchases, enhances customer engagement, and strengthens loyalty through more personalized relationships. Keywords: digital marketing, sales, customer loyalty, Somethinc